Carbon quantum dots as corrosion inhibitors - Soni A.; Malviya M.; Tiwary D. (My University, 2025)
This review comprises the various preparations of carbon quantum dots (CQDs) through different methods and their application in different metal corrosions. The CQDs are prepared from different green sources, various chemicals, metal oxides, etc. It is also found that when it is doped or codoped with nitrogen and sulfur, its efficiency is increased toward various applications like sensing, metal corrosion, bioimaging, drug delivery, etc. In this review, we summarize the corrosion inhibition effect of various CQDs. (figure Presented) © 2023 Elsevier Inc. All rights reserved.